2020
DOI: 10.1073/pnas.2006089117
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to news grows less fragmented with an increase in mobile access

Abstract: The abundance of media options is a central feature of today’s information environment. Many accounts, often based on analysis of desktop-only news use, suggest that this increased choice leads to audience fragmentation, ideological segregation, and echo chambers with no cross-cutting exposure. Contrary to many of those claims, this paper uses observational multiplatform data capturing both desktop and mobile use to demonstrate that coexposure to diverse news is on the rise, and that ideological self-selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 29 publications
3
40
0
1
Order By: Relevance
“…While social media use may broadly be associated with more diverse news diets Yang et al, 2020) and higher levels of political participation, engagement, and expression (Boulianne, 2019), they are also associated with a range of problems, including attempts to artificially shape the public agenda (Vargo et al, 2018), spread disinformation (Grinberg et al, 2019), or inflate the popularity of specific candidates (Allcott & Gentzkow, 2017). Social media activities may also contribute to the polarization of political debates and stoke incivility in the public sphere (Stella et al, 2018;Theocharis et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While social media use may broadly be associated with more diverse news diets Yang et al, 2020) and higher levels of political participation, engagement, and expression (Boulianne, 2019), they are also associated with a range of problems, including attempts to artificially shape the public agenda (Vargo et al, 2018), spread disinformation (Grinberg et al, 2019), or inflate the popularity of specific candidates (Allcott & Gentzkow, 2017). Social media activities may also contribute to the polarization of political debates and stoke incivility in the public sphere (Stella et al, 2018;Theocharis et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This would lead to a better depiction of media consumption patterns in comparison to filling out an (online) survey (Möller et al 2019in Geers 2020. Another upheaval when questioning news consumption could be that a large number of people access news outlets, not only to consume hard news but mostly for entertainment purposes (Yang et al 2020). Hence, taking up preferred news topics would compose a more detailed news repertoire.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to research endeavours driven by methodological innovations in the area of network science that have analyzed behavioral trace data to address many of the debates that had characterized the early literature on online news. One such line of research has shown how online consumption is really not "decentralized" as many early internet evangelists had speculated (Mukerjee, Majó-Vázquez, & González-Bailón, 2018), even though it is more diverse (Yang, Majó-Vázquez, Nielsen, & González-Bailón, 2020).…”
Section: Online News Consumption Researchmentioning
confidence: 99%